CONFORMITY OF TECHNOLOGIES OF MELTING AND CASTING OF OXYGEN-FREE COPPER TO THE MODEM REQUIREMENTS - Ten E. B.; E. I. Marukovich; S. R. Chudakov (Литьë и металлургия)
The device, preventing mixing of insufficiently refined melt with refined one, and also device for continuous blowout of liquid copper by inert gas in melting furnace mixer is worked out.